1988
DOI: 10.1254/jjp.48.463
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Blocking Action of Franidipine Hydrochloride (CV-4093-2HCI) In Vitro and In Vivo

Abstract: Abstract-The calcium-channel blocking action of franidipine (CV-4093.2HCI) was investigated in vitro and in vivo. CV-4093.2HCI inhibited the 60 mM K+ induced contraction of rabbit aorta and those of coronary, renal, mesenteric and femoral arteries of dog less potently than nifedipine and nicardipine. In dog portal and femoral veins, CV-4093.2HCI inhibited K+-induced contraction as potently as nifedipine and nicardipine did. The inhibitory effect of this drug was fully developed by pretreatment for 60 min, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In our study, CV-4093 elicited a long-lasting hypotensive action in anesthetized SHRSP and was more potent than nicardipine in this firmly to the site of action, which is considered to be responsible for the long-lasting hy potensive action of the compound (4,12). UF, UNa ,V and FENa after the higher dose of CV-4093 disappeared between 1-1.5 hr after the injection (Table 3), after which the three variables remained at their respective control levels, in contrast to the compound's long lasting hypotensive and renal vasodilating effects.…”
Section: Discussionmentioning
confidence: 47%
“…In our study, CV-4093 elicited a long-lasting hypotensive action in anesthetized SHRSP and was more potent than nicardipine in this firmly to the site of action, which is considered to be responsible for the long-lasting hy potensive action of the compound (4,12). UF, UNa ,V and FENa after the higher dose of CV-4093 disappeared between 1-1.5 hr after the injection (Table 3), after which the three variables remained at their respective control levels, in contrast to the compound's long lasting hypotensive and renal vasodilating effects.…”
Section: Discussionmentioning
confidence: 47%
“…Moreover, it has been reported that, as compared with nicardipine, the antagonizing effect of CV-4093.2HC1 on potassium-induced vasocontraction was more marked in the isolated kidneys including the arterioles but less in the isolated large renal artery (20). Furthermore, the antagoniz ing effects of CV-4093.2HC1 on potassium induced vasocontraction were less prominent than those of other calcium antagonists in the aorta and coronary artery of dogs and rabbits (20). These findings suggest that CV-4093• 2HCI has a higher affinity for the resistant vessels (arterioles and small arteries) in the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…One is the influx of extracellular cal cium ions through the cell membrane and the other is the release from the intracellular cal cium store (11). Many studies support the view that the vasodilative and calcium antago nistic activities of dihydropyridine calcium antagonists result from blocking the calcium influx through L-channels (8,12). Although movement of calcium ions through L-channels has not been directly measured in the previous studies, continuous suppression of vascular contraction brought about by long-lasting cal cium antagonists is generally assumed to result from prolonged suppression of L-channels.…”
mentioning
confidence: 97%
“…In the preparation treated with FRC-8653, inhibition persisted through out the experimental period and approximate ly 70% suppression was still observed 7 hr af ter removal of the drug. Several laboratories have studied the long acting effects of dihy dropyridine calcium antagonists (8)(9)(10) As sources of increased intracellular cal cium, two major mechanisms have become evident. One is the influx of extracellular cal cium ions through the cell membrane and the other is the release from the intracellular cal cium store (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation